Principles of project management in development of research and educational activities in the leading russian universities - Vasiliy M. Zhurakovsky (Высшее образование в России)
The article focuses on the results of the project management principles implementation in the realization of the development programs at the leading Russian universities. The experience in the sphere of scientific and educational activities management within the network of federal and national research universities is considered.